2016
DOI: 10.1590/1679-78252872
|View full text |Cite
|
Sign up to set email alerts
|

One-Way Shear Resistance of RC Members with Unconnected Stirrups

Abstract: This paper presents results of eight experimental tests carried to evaluate the mechanical performance of unconnected "W" stirrups.Reinforced concrete wide beams were tested and their characteristics were idealized to represent column strips in flat slab buildings. The main variables were: the type of shear reinforcement; the shear span to effective depth ratio (av/d); and the flexural (ρl) and shear (ρw) reinforcement ratios. In general, both the response and the shear resistance of the structural elements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…It was observed that all tested beams had an ultimate strength lower than the estimated flexural strength, contributing to the understanding that the specimens' failure was related to shear. Concerning the comparison with the reference beam, all specimens showed a significant increase in strength, varying between 89% and 158%, showing that the prefabricated truss stirrups contribute to the increase in shear strength, as observed by Ferreira et al [22]. The beams with supplementary reinforcement at both end showed greater strength than the specimens with the u-hooks only on the tensile face.…”
Section: Ultimate Strength and Theoretical Estimatessupporting
confidence: 62%
See 3 more Smart Citations
“…It was observed that all tested beams had an ultimate strength lower than the estimated flexural strength, contributing to the understanding that the specimens' failure was related to shear. Concerning the comparison with the reference beam, all specimens showed a significant increase in strength, varying between 89% and 158%, showing that the prefabricated truss stirrups contribute to the increase in shear strength, as observed by Ferreira et al [22]. The beams with supplementary reinforcement at both end showed greater strength than the specimens with the u-hooks only on the tensile face.…”
Section: Ultimate Strength and Theoretical Estimatessupporting
confidence: 62%
“…The longitudinal reinforcement was kept constant for all tested beams, consisting of 7 bars of 25 mm in diameter in the tensile area and 7 bars of 12.5 mm in diameter in the compression area. The shear reinforcement used in this study was composed of prefabricated truss stirrups, developed by Ferreira et al [22], manufactured in modules and installed between the bottom and top flexural reinforcement shown in Figure 4a. In addition to the transverse reinforcement, u-hook-shaped delamination control reinforcement was used, according to the model adopted by Tapajós [13], as shown in Figure 4b.…”
Section: Experimental Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Although various types of shear reinforcement have been shown to increase punching resistance capacity and increase the ductility of slab-column connections, in comparison to similar slabs without shear reinforcement, [36][37][38][39][40][41][42] the normative requirements of ACI 318, 43 ACI 421.1R, 44 Eurocode 2, 45 ABNT NBR 6118, 46 and the recommendations of the fib Model Code 2010 47 determine that the reinforcements should be well anchored. More specifically, in the case of stirrups, ACI 318 42 mentions that shear reinforcement should involve the flexural reinforcement in the direction of the detailing.…”
Section: Introductionmentioning
confidence: 99%